Efektifitas Intervensi Edukasi Gizi Berbasis Smartphone dalam Keberhasilan Praktek ASI Eksklusif: Meta Analisis: Efektifitas Intervensi Edukasi Gizi Berbasis Smartphone dalam Keberhasilan Praktik ASI Eksklusif: Meta Analisis - Rachmahnia Pratiwi; Dominikus Raditya Atmaka; Deandra Ardya Regitasari Sutoyo; Trias Mahmudiono (Universitas Airlangga, 2023)
Background: Exclusive breastfeeding is the cornerstone of infant health and one of the 2030 Sustainable Development Goals (SDGs). The advancement of information technology can be used to promote health, and providing information through messages on smartphone applications can improve breastfeeding awareness and adherence. Objectives: To determine which social media platforms effectively promote exclusive breastfeeding through nutrition education interventions. Methods: This study employed a meta-analysis method. The terms “breastfeeding,” “social media,” and “smartphone” were used to search for articles in multiple electronic journals, such as Scopus, PubMed, ScienceDirect, and Google Scholar. Articles that provide an intervention using smartphone media for groups of expectant mothers who wish to breastfeed their babies and mothers who have ceased breastfeeding and want to resume were selected. Forest plot analysis was performed using the STATA 12. Results: From 2018 to 2021, seven articles were obtained, with research conducted in the United States, India, Indonesia, Israel, and Brazil. The study’s findings revealed that a nutritional education intervention using Smartphones led to an average success rate of exclusive breastfeeding between the intervention group and the control group of 1.23 (7 studies), 95% CI (1.08 - 1.39); P = 0.000; and I2 = 97.1%. Conclusions: Intervention using smartphones by sending short messages daily and counselling by telephone every week can increase mothers’ knowledge and ability to provide exclusive breastfeeding to their infants. An intervention using smartphones to transmit daily text messages and weekly telephone counselling could enhance mothers’ knowledge and ability to breastfeed their children exclusively.